Beyond the Global Agenda - Abubakar Eby Hara; Suyani Indriastuti; Agus Trihartono (University of Jember, 2022)
This article examines how state and religious non-state actors understand and make efforts to overcome human security challenges in Indonesia. The activities of these actors are largely outside the UNDP global human security agenda because they have been conducted long before the concept of human security was popularised. The authors seek to reinterpret the concept of human security as a paradigm to make it more attuned to the experience of the state and religious non-state actors when dealing with human security challenges in the Indonesian context. Data from primary and secondary sources gathered in Indonesia in 2021 reveals that religious motivations and environmental threats drive the agendas of religious non-state actors operating in Indonesia. Keywords: Human Security, Religious non-state actor, norm diffusion, UNDP, and Indonesia.